Trust Deterioration in an International Buyer-Supplier Relationship - Bell, Geoffrey G. (Journal of business ethics, 2002)
Despite an abundance of research on inter-organizational trust, researchers are only beginning to understand the process of trust deterioration as an inter-organizational phenomenon. This paper presents a case study examining the deteriorating relationship between two international high-tech firms. We surveyed respondents from the supplier firm to identify major elements that reduced the supplier's trust in its customer, using the dimensions of trust identified by Mayer et al. (1995). While violations of ability, integrity, and benevolence all contributed to trust reduction, early violations of trustee benevolence contributed importantly to trust deterioration. Over time, the relationship became "sensitive," and respondents reported many incidents of trust violation. Managers reported primarily integrity- and benevolence-related incidents, while no pattern emerged among operations personnel. We examine the results in light of Hosmer's (1995) ethically-based trust principles. The supplier and customer would likely differ in their opinion of whether the customer was acting "ethically." This suggests that scholars need to examine how many principles can be violated before trust is eliminated, and whether any of the principles are particularly salient in business relationships.